2020
DOI: 10.15243/jdmlm.2021.082.2601
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of soil moisture storage in clove plantation land using biopore technology and organic material litters

Abstract: The biopore infiltration hole with organic material litter can increase the soil capacity to accommodate and store soil moisture. This study was aimed to determine the effect of biopores and organic material litter on soil moisture storage and the relationship of climatic conditions on soil moisture storage. The experiment was carried out on clove plantations on Ternate Island, North Maluku from December 2018 to February 2019. This study used a factorial randomized block design. The first factor was the biopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…There are wet months (surplus) and dry months (deficit) in climatic conditions, so that rainwater harvesting technology is needed during a surplus period for water reserves during a deficit. As the research by Umasugi [22] biopore infiltration holes with a depth of 50 cm with clove leaf litter can reduce surface runoff to 0.1 mm / rain, increase soil organic matter by 4.28% and increase soil moisture storage by 304.9 mm. Plant litter as source of organic matter can meet the water requirements of plants in the dry season [25].…”
Section: G Water Management For Clove Plantation During Dry Seasonmentioning
confidence: 92%
See 3 more Smart Citations
“…There are wet months (surplus) and dry months (deficit) in climatic conditions, so that rainwater harvesting technology is needed during a surplus period for water reserves during a deficit. As the research by Umasugi [22] biopore infiltration holes with a depth of 50 cm with clove leaf litter can reduce surface runoff to 0.1 mm / rain, increase soil organic matter by 4.28% and increase soil moisture storage by 304.9 mm. Plant litter as source of organic matter can meet the water requirements of plants in the dry season [25].…”
Section: G Water Management For Clove Plantation During Dry Seasonmentioning
confidence: 92%
“…Andisols generally dominated the soil in the research site. The research by Umasugi [22], showed that the soil content weight in clove plantations was generally <0.9 g/cm 3 , the texture from clay to clay was dusty on the top layer, and sandy on the lower layer, which indicated that the soil was light and developed from pyroclastic and Volcanic ash of Mount Gamalama. Such soil characteristics will result in low available moisture in the soil and around the root area since water is easily lost due to evaporation and percolation.…”
Section: B Soil Conditions and Moisture Availabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…Lubang Resapan Biopori Berkompos (LRBB) merupakan teknologi lubang resapan yang dibuat di permukaan tanah hingga kedalaman tertentu, dapat menampung runoff air hujan dan menjadi tempat untuk dekomposisi bahan organik (Permatasari 2015). Beberapa penelitian menunjukkan bahwa LRBB dapat diaplikasikan untuk mengurangi volume runoff (Landl et al 2018;Clunes et al 2021), meminimalkan kehilangan hara dan meningkatkan daya simpan air (Landl et al 2019), meningkatkan porositas tanah (Reck et al 2018), meningkatkan kapasitas air tersedia (Umasugi et al 2021) dan meningkatkan kapasitas infiltrasi (Widiya dan Krisnawati 2017;Santos et al 2018). Kompos yang terdapat pada LRBB diharapkan mampu membantu ketersediaan hara dalam tanah di sekitarnya.…”
Section: Pendahuluanunclassified